Impact of oral chronic administration of sildenafil in children and young adults after the Fontan operation. (September 2011) - Ciliberti, Paolo; Giardini, Alessandro
Evaluation of: Goldberg DJ, French B, McBride MG et al. Impact of oral sildenafil on exercise performance in children and young adults after the Fontan operation: a randomized, double-blind, placebo-controlled, crossover trial. Circulation 123, 1185–1193 (2011). After the Fontan operation, patients often have decreased exercise capacity as a result of an inability to increase cardiac output during exercise. Evidence exists that limitation in ventricular preload, related to pulmonary artery resistance plays an important role. A drug able to decrease pulmonary vascular resistance might increase transpulmonary flow and ventricular preload, therefore improving cardiac output and exercise performance. The article by Goldberg et al. is the first randomized, double-blind, placebo controlled, crossover trial to evaluate the impact of the phosphodiestarase-5 inhibitor sildenafil on exercise performance in patients after they have received the Fontan operation. The study included 28 patients with a mean age of 14.9 years. In this population, 6 weeks of sildenafil administration significantly improved ventilatory efficiency. The authors also noted an increase in exercise capacity during submaximal exercise, after 6 weeks of sildenafil in those patients with single left or mixed ventricular morphology and in those with more advanced heart failure (baseline serum brain natriuretic peptide level >100 pg/ml). The drug was well tolerated with no significant side effects. These findings suggest that sildenafil may play a role in improving exercise performance and exercise-induced breathlesness in children and young adults with single-ventricle physiology after the Fontan operation. Additional data on the possible benefit in terms of long-term clinical outcome and safety of sildenafil in this setting are needed.